The The Effect of the “Siaga” Website on Husband's Behavior in Childbirth Assistance at Afah Fahmi's TPMB Surabaya - Devi Annisa; Evi Pratami; Dina Isfentiani; Kharisma Kusumaningtyas; Mohammed Ismath (International Journal of Advanced Health Science and Technology, 2024)
Childbirth is the process of expelling the products of conception (fetus and placenta) that are full-term or nearly full-term and can live outside the womb through the birth canal or without assistance using their own strength. The smooth running of a delivery is influenced by the presence of a companion who is able to provide the support expected by the birthing mother. During this time the husband feels uncomfortable and incompetent to meet the physical or emotional needs of his wife during childbirth. Lack of support and attention by husbands results in many wives experiencing stress during childbirth. The purpose of this study was to analyze the effect of the "standby" website on husband's behavior in childbirth assistance. The research design used was a one-group pretest-posttest design with a population of husbands from Trimester 3 pregnant women of 110 people with a sample of husbands from pregnant women Trimester 3 HPL in February-March. Sampling by purposive sampling of 40 samples. Data collection using a questionnaire. Data analysis used the Wilcoxon signed rank test with α=0.005. The results obtained were p = 0.000 and there was an average increase of 3.08 at the knowledge level, p = 0.000 and an average increase of 6.83 at the attitude level and p = 0.001 and an average increase of 22.78 at the action level. The results showed that the "Siaga" website affects husband's knowledge because the "Siaga" website has a lot of information and insights about childbirth assistance, influences the husband's attitude because the "Siaga" website is modeled as easy for husbands to learn, influences husband's actions because the "Siaga" website has many features. regarding birth assistance. The conclusion from this study is that there is an influence of the "Siaga" website on the husband's knowledge in childbirth assistance, there is an influence of the "Siaga" website on the husband's attitude in childbirth assistance, there is an influence of the "Siaga" website on the husband's actions in childbirth assistance. Suggestions from this study for educational institutions and health workers, namely as part of health promotion media and applied in the learning process. Suggestions for future researchers as a source of existing website development literature. Keywords: website, behavior, childbirth assistance.